Circuits on Cylinders - Hansen, Kristoffer Arnsfelt; Miltersen, Peter Bro; Vinay, V. (BRICS Report Series, 2002)
We consider the computational power of constant width polynomial size cylindrical circuits and nondeterministic branching programs. We show that every function computed by a Pi_2 o MOD o AC^0 circuit can also be computed by a constant width polynomial size cylindrical nondeterministic branching program (or cylindrical circuit) and that every function computed by a constant width polynomial size cylindrical circuit belongs to ACC^0.